Executive Committee Minutes 2007-03-15 - Academic Senate:::::::::
Urgent Charge for FSSP and Discussion about current IDC conditions, Revision to Counseling Program, Formal Dispute Resolution Procedures, Request to survey School representatives at the Senate, Electronic communication with faculty, Engineering Program curriculum revision